Detection of a Putative Novel Papillomavirus Type within a Large Exophytic Papilloma on the Fetlock of a Horse - John S. Munday; Michael R. Hardcastle; Melissa Sim (Pathogens, 2020)
A 10-year-old horse presented with two 3-cm diameter exophytic masses over the fetlock. Histology was consistent with a hyperplastic squamous papilloma and numerous cell changes consistent with papillomavirus (PV) infection were visible. Partial sequences of PV L1 and E1 ORFs were amplified using consensus PCR primers. The sequences were most similar to Equus caballus type 1 (EcPV1). However, as the sequences were only around 73% similar to EcPV1, they appear to be from a novel PV type that is likely to be within the Zetapapillomavirus genus. The papillomas were treated with topical imiquimod and resolved within 14 weeks. The clinical presentation of the papillomas in the present case had marked differences to the clinical presentation of EcPV-1-induced papillomas, which are typically small, numerous and around the face. Observations from the present case increase the clinical spectrum of PV-induced lesions in this species as well as providing evidence of an additional novel papillomavirus that is able to cause disease in horses.